The evaluation of dowel-bearing properties of laminated bamboo parallel to grain. (June 2020) - Cui, Zhaoyan; Tu, Liuhui; Xu, Ming; Chen, Zhongfan; Wang, Chenxi
Abstract: The dowel-bearing tests were conducted to investigate the embedding strength of laminated bamboo parallel to grain for the design of dowel-type connections according to ASTM D 5764-97a. The embedding strength is evaluated by the 5% diameter off-set method and the maximum embedding strength is determined by the ultimate load. The effects of the specimen size, the loaded length and the bamboo strip arrangements on the test results have been discussed. The embedding strength decreases gradually with the increase of the thickness and the loaded length. The difference in embedding strength for different bamboo strip arrangements is negligible. The two typical failure modes and corresponding load-displacement curves have been analyzed. The theoretical results of embedding strength in different national standards have been compared with each other, and the calculation equation among dowel diameter and compressive strength parallel to grain is proposed by regression analysis of the test data. It presents a better prediction for the embedding strength of laminated bamboo.